Development and psychometric testing of the nursing practice difficulty scale for nurses caring for patients with dementia in general hospitals - Ting Liu; Hisae Nakatani; Huifang Chen; Nan Gao (Elsevier, 2024)
Objective: As aging in the Chinese population increases, the hospitalization rates of patients with dementia have also risen. Research on the difficulties of nurses who care for patients with dementia in Chinese general hospitals is limited. This study aimed to develop a scale to measure the difficulties nurses face in nursing patients with dementia in Chinese general hospitals and to verify its reliability and validity. Methods: Guided by the biopsychosocial theory, an initial scale was created through a literature review, qualitative interviews, and expert consultation. A web-based survey for psychometric testing was conducted with 394 nurses from 11 general hospitals during September to November 2021. Validity was verified using content validity, exploratory factor analysis, the known-groups method, and concurrent validity. Cronbach's α coefficient and split-half reliability were used to assess reliability. Results: The Item-level Content Validity Index was 0.833-1.000. The Scale-level Content Validity Index was 0.929. Twenty-one items with four factors were extracted from the item analysis and exploratory factor analysis. According to the known-groups method, the difficulty of the experienced group and the group with training experience was significantly lower than that of the less experienced group and the group without training experience. Based on external standards, the correlation coefficient was 0.387 with the Nursing Job Stress Scale and −0.239 with the Dementia Care Attitude Scale. Cronbach's α coefficient for each factor ranged from 0.889 to 0.905, and the total was 0.959. The split-half reliability for each factor ranged from 0.814 to 0.894, and the total was 0.911. Conclusion: This study discovered a four-factor structure related to the difficulty scale of dementia nursing practice, and the scale's reliability and validity were confirmed. The scale can be utilized to assess the difficulty of dementia nursing practice in general hospitals and may be employed in future research to improve dementia nursing practices.